Chaperone-mediated folding and maturation of the penicillin acylase precursor in the cytoplasm of Escherichia coli - Xu, Y. L.; Weng, C. L.; Narayanan, N.; Hsieh, M. Y.; Anderson, W. A.; Scharer, J. M.; Moo-Young, M.; Chou, C. P. (Applied and Environmental Microbiology, 2005)
Expression of the leaderless pac gene (LL pac), which lacks the coding region for the signal peptide of penicillin acylase (PAC), in Escherichia coli was conducted. It was demonstrated that the PAC precursor, proPAC, can be produced and even processed to form mature PAC in the cytoplasm, indicating that the posttranslational processing steps for PAC maturation can occur in both the periplasm and the cytoplasm of E. coli. The outcome of proPAC folding and PAC maturation could be affected by several factors, such as inducer type, proPAC formation rate, and chaperone availability. Misfolding of proPAC in the cytoplasm could be partially resolved through the coexpression of cytoplasmic chaperones, such as trigger factor, GroEL/ES, or DnaK/J-GrpE. The three chaperones tested showed different extents of the effect on proPAC solublization and PAC maturation, and trigger factor had the most prominent one. However, the chaperone-mediated solublization of proPAC did not guarantee its maturation, which is usually limited by the first autoproteolytic step. It was observed that arabinose could act as an effective inducer for the induction of LLpac expression regulated by the lac-derived promoter system of trc. In addition, PAC maturation could be highly facilitated by arabinose supplementation and coexpression of trigger factor, suggesting that the coordination of chaperone systems with proper culture conditions could dramatically impact recombinant protein production. This study suggests that folding/misfolding of proPAC could be a major step limiting the overproduction of PAC in E. coli and that the problem could be resolved through the search for appropriate chaperones for coexpression. It also demonstrates the analogy in the issues of proPAC misfolding as well as the expression bottleneck occurring in the cytoplasm (i.e., LL pac expression) and those occurring in the periplasm (i.e., wild-type pac expression).